Sanitary management and pulmonary lesions in pigs in Metropolitan Recife and the Coastal Zone of the state of Pernambuco, Brazil - d'Alencar, Alessandra Santos; Farias, Marcia Paula de Oliveira; Rosas, Eduardo de Oliveira; Lima, Marilene Maria de; Menezes, Mário Martins; Santos, Fernando Leandro dos; Alves, Leucio Câmara; Faustino, Maria Aparecida da Gloria (Semina: Ciências Agrárias, 2011)
The objective of the present study was to determine the main lesions found during the sanitary inspection of the lungs of slaughtered pigs. The study was carried out at three slaughterhouses registered with the Pernambuco State Inspection System located in metropolitan Recife and the coastal zone of the state of Pernambuco, Brazil. A total of 715 pig lungs were inspected from July 2008 to May 2009. Pulmonary lesions were detected in all herds studied. Among the total number of animals evaluated, 43.8% (313/715) had some type of lung injury. Pneumonia was the most common finding, recorded in 93.0% (291/313) of damaged lungs, followed by petechial hemorrhaging (6.7%; 21/313) and blood aspiration (3.5%; 11/313). Among the lungs submitted to histopathology, the most frequent microscopic finding was granulomatous pneumonia with 32.2% (49/152), followed by 21.7% (33/152) of interstitial pneumonia and 3.2% (14/152) fibrinous bronchopneumonia. There was a significant association between the occurrence of lung lesions and all variables related to the environment in which the animals were raised as well as the type of operation and nutritional status.